Enhancing Sound Governance in Sport Policy through the Sport Potential Card Program in Bojonegoro - Pradhana Hamdhallah Suryohayati; Ana Kumalasari; Rupiarsieh Rupiarsieh; Hoby Nasandratra Andriamiandrisoa (Universitas Lambung Mangkurat, 2025)
This research examines the application of sound governance principles in improving the effectiveness of the Leveled Sports Potential Card (K'POB) program in Bojonegoro Regency. This program aims to capture and develop young athletes through providing incentives and sustainable coaching. The method used in this research is descriptive qualitative with interview and observation techniques. The results of this study indicate that implementing K'POB still needs various challenges, such as lack of supervision, misuse of incentives, and complex program structure. However, applying sound governance principles can increase the success of this program by strengthening synergies between government and non-government institutions, improving supervision, and expanding information distribution to remote areas. K'POB can be an effective solution for the sustainable development of young athletes. This research contributes to improving sports policy based on sound governance. This research has limitations that lie in a limited scope. Since this research focuses on a specific program in Bojonegoro Regency, the findings may not be generalizable to other regions.